PEMODELAN KUANTITATIF UNTUK ANALISIS HUBUNGAN POLA ASUH DENGAN STATUS GIZI BALITA DI KABUPATEN BANYUMAS - Rahardjo, Setiyowati; Kuswanto, Kuswanto; Aprilianingrum, Farida (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2008)
Take  care children are something need to achieve growth and nutritional status optimally . the role of take care children  determinan to children growth were important, good take care children can increasing nutritional staus and children health. This research aimed to study the correlation between take care children and nutritional status pf children under5 years. Research design implemented was case cobtrol. Total sample 92 children under 5 year with 23 severaly malnutritional status. Data collection by ibterviewed to their mother with structured questioners. Data analysis with ubivariabt, bivariate and multivariate analysis. Descriptiveanalysis showed that in saverely malnourished case study, most (73*=%) mother taje careof children are middle, 66,7% mother have middle nutrition knowledge, 95,7 % mother have low education level, 53,6% children were infection disease and capability of food health accessibility expenditures have average Rp. 130.000,-. In moderately malnourished case stidy , most (62,3%) mother take care of chikdren are middle 69,6% mother have middle nutrition knowledge 89,9%mother have low education level, 53,6% children were infection disease, and capability of food health accessibility expenditures have avarege Rp/ 129.700,00. In severely malnourished and moderately malnourished case study there was correlation between mother taej care children withnutritional status of children after attent by capability pf food health accessibility expenditures and mother education level. It recommended to mother always monitoring ther chikdren nutritional status by routin activity in posyandu, give food for fulfill theur nutrition need.